ANALISIS EFEKTIFITAS PENGGUNAAN ANGGARAN BELANJA LANGSUNG DAN BELANJA TIDAK LANGSUNG DALAM PENERAPAN ANGGARAN BERBASIS KINERJA PADA DINAS SOSIAL KABUPATEN MUSI BANYUASIN - Jumania Septariani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2019)
This study describes the principles of performance-based budgeting on Dinas Sosial district of Musi Banyuasin, knowing the effectiveness of the use of direct expenditure and indirect spending in Dinas Sosial district of Musi Banyuasin as well as budget performance. The method used in this research is qualitative method with descriptive approach. Data collecting technique is done through field study that is interview, documentation and literature study. Data analysis techniques starting from quantitative and qualitative with descriptive approach. The results of this study indicate that the principles of performance – based budgeting on Dinas Sosial district of Musi Banyuasin stated that tranparency and accountability is still no good, but the budget discripline and budget justice are good enough. The effectiveness of the use of direct expenditure in the implementation of performance–based budgets. Based on the ratio of effectiveness of the use of the budget Dinas Sosial district of Musi Banyuasin years 2014 up to the year 2016 has effective criteria and from year to year the level of effectiveness has increased. The effectiveness of the use indirect budget from 2014 to 2016 has a fairly effective criteria and from year to year always fluctuate.